The Diagnostic Utility of RAS Q61R Mutation-specific Immunohistochemistry in Epithelial-Myoepithelial Carcinoma. (July 2021) - Nakaguro, Masato; Tanigawa, Maki; Hirai, Hideaki; Yamamoto, Yoshinari; Urano, Makoto; Takahashi, Reisuke H.; Sukeda, Aoi; Okumura, Yuki; Honda, Shogo; Tasaki, Koichiro; Shimizu, Akira; Tsukahara, Kiyoaki; et al.
Abstract : Epithelial-myoepithelial carcinoma (EMC) is a rare salivary gland cancer characterized by biphasic tubular structures composed of inner ductal and outer clear myoepithelial cells. Because of its histologic variety and overlap of histologic features with other salivary gland tumors, there are broad differential diagnoses. The HRAS Q61R mutation has been reported to be frequent in and specific to EMC. We evaluated the usefulness of RAS Q61R mutant-specific immunohistochemical (IHC) staining for detecting this genetic alteration in EMC. We investigated 83 EMC cases and 66 cases of salivary gland tumors with an EMC-like component, including pleomorphic adenoma, adenoid cystic carcinoma, basal cell adenoma/adenocarcinoma, and myoepithelial carcinoma. Sanger sequencing was performed for HRAS, KRAS, and NRAS . The diffuse and membranous/cytoplasmic RAS Q61R IHC expression was observed in 65% of EMC cases, in which all cases harbored the HRAS Q61R mutation. IHC-positive cases were present only in de novo EMCs (54/76 cases, 71%) but not in EMCs ex pleomorphic adenoma. The immunoreactivity was almost always restricted to the myoepithelial cells. Conversely, all EMC cases lacking the HRAS Q61R mutation were negative on IHC. In addition, only 3% of EMC-like tumors showed the abovementioned immunopositivity. None of the cases examined carried KRAS or NRAS mutations. IHC for RAS Q61R is highly sensitive and specific for detecting the HRAS Q61R mutation in EMC. Since significant immunopositivity was almost exclusively identified in nearly two thirds of EMCs but seldom in the histologic mimics, the IHC of RAS Q61R is a useful tool for diagnosing EMC in general pathology laboratories. Abstract : Supplemental Digital Content is available in the text.